LANDASAN HUKUM DALAM PEMILIHAN UMUM KEPALA DAERAH Kajian : Landasan Hukum Penggantian Calon Wakil Gubernur Kaltim Masa Bakti 2013-2018 - Gabriel Gajah Tukan (Universitas 17 Agustus 1945 Samarinda, 2013)
The aim of this research is to know the legal fact of the substitution of the candidate of vice governor of East Kalimantan province based on the principle the the technical realization of general election of the regional leader Number 9, 2012. The method of it is qualitative one. The data is taken from the Tribun Kaltim Daily News and Tepian TV Samarinda news on Thursday, June 20,2013. The data of the research is that after the candidates of Governor and vice Governor namely Farid Wadjdy and Aji Sofyan Alex. The first nama is supported by the Unity development party (PPP) political party either from the Centrak Committee in Jakarta but the second is supported by regional of East Kalimantan committee of Democratic Indonesian Party (PDIP). The problem is that the second candidate is not supported by the central committee of PDIP party. Consquently he is dismissed as the chairman of regional of East Kalimantan committee of Democratic Indonesian Party (PDIP) as well as being substituted by the one, Siswadi, who is the successful and promising cader of Samarinda Democratic Indonesian Party ( PDIP). He is supported by the central party to be the candidate concerned. Here, the researcher will prove by the legal opinion.